Food selectivity and neophobia in children with autism spectrum disorder and neurotypical development: a systematic review - Rodrigues, Joao Victor S. [UNESP]; Poli, Maria Clara F. [UNESP]; Petrilli, Pedro H. [UNESP]; Dornelles, Rita Cassia M. [UNESP]; Turcio, Karina H. [UNESP]; Theodoro, Leticia H. [UNESP] (Oxford Univ Press Inc, 2023)
Context Individuals with autism spectrum disorder (ASD) have common eating problems, including food refusal, dietary restrictions, and behavioral problems during eating. Objective The aim of this systematic review was to find more clear evidence on the relationship between food selectivity or food neophobia (FN) and ASD in children up to age 14 years. The PECO-based question was: Are food selectivity and FN behaviors more prevalent in children with ASD than in children with neurotypical development (NTD)?, in which the P is children, E is ASD, C is children with NTD, and O is food selectivity and FN. Data sources Clinical studies in the databases PubMed, Embase and Web of Science, comparing children with ASD and those with NTD, were reviewed from October 1966 to October 2021. Study selection and data extraction A total of 122 studies were analyzed for summary reading, and only 17 of these were included in the descriptive qualitative analysis. In 9 studies, the analysis of food selectivity was performed via a questionnaire. Results The results showed that children with ASD are more selective than those with NTD. Four studies evaluated FN through scales; however, only 2 found higher levels of FN in the ASD group than in children with NTD. The sensory profile was measured using questionnaires in 9 studies, and we found that altered sensory processing is more common in children with ASD. Conclusion Children with ASD present greater food selectivity than children with NTD. However, the occurrence of FN was higher in only 50% in which FN was investigated, which points to a need for studies that compare FN between siblings with ASD and those with NTD in the same family nucleus. In addition, atypical oral sensitivity seems to be a sensory characteristic most related to eating disorders. Systematic Review Registration PROSPERO registration no. CRD42021247880.
Keywords: autism spectrum disorder; children; food selectivity; neophobia